Vasco da Gama - Knight, David C.; Sottung, George (Mahwah, N.J. : Troll Associates, 1979)
A brief biography of the first European to sail around the Cape of Good Hope to India.
School Library Journal
4.3
3-6
Keywords: Gama, Vasco da, -- 1469-1524 -- Juvenile literature; Gama, Vasco da, -- 1469-1524.; Gama, Vasco da, -- 1469-1524.; Explorers -- Portugal -- Biography -- Juvenile literature; Explorers; Explorers -- Biography